The Effect of Communication, Work Discipline and Work Environment on Employee Performance at Hotel Imani Kuta Bali - Hedy Wartana, I Made; Eli Sumerta, I Ketut (Jurnal Manajemen Pelayanan Hotel, 2023)
The tourism industry is one of the economic supports of the Indonesian state, especially Bali. The tourism industry sector provides many opportunities to improve the economy of the Balinese people. In this regard, it is very important to manage and develop optimally in the tourism sector. Bali has its own charm both because of its culture, customs and natural wealth so that tourists make Bali as one of the tourist destinations. To provide comfort and security while tourists are on vacation in Bali, one of the hotels in the Kuta area, namely Hotel Imani provides the best facilities This research was conducted at Hotel Imani Kuta Bali with a sample of 48 employees. The sampling technique in this study was to use the census method or saturated sampling. Data collection with the distribution of questionnaires using a likert scale with a score of 1-5. The data analysis technique used in this study is a multiple linear regression analysis technique with the Statistical Package Social Science (SPSS) version 24.0 test. The results of this study show that Communication (X1) has a positive and significant effect on Employee Performance (Y) at Hotel Imani Kuta Bali. Work Discipline (X2) has a positive and significant effect on Employee Performance (Y) at Hotel Imani Kuta Bali. The work environment has a positive and significant influence on Employee Performance (Y) at Hotel Imani Kuta Bali. The contribution of the large influence of communication, work discipline and work environment in influencing employee performance at Hotel Imani Kuta Bali by 56.7% and the remaining 43.3% was influenced by other variables that were not analyzed in this study. Meanwhile, the work discipline variable has the most dominant influence in influencing employee performance at Hotel Imani Kuta Bali. To find out other variables that affect employee performance, it is hoped that further research is expected to examine other variables that can affect employee performance. Keywords: Communication, Work Discipline, Work Environment, Employee Performance.